Pola Pertumbuhan Ikan Pari Kemejan (Rhynchobatus springeri) yang Didaratkan di Kubu Raya, Kalimantan Barat - Hadinata, Fitra Wira; Rahayu, Sri; Nurleha, Fitri; Gloria A.R., Kezia; Benaya M.S. (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2021)
The whitespotted guitarfish (Rhyncobatus Springeri) resource is an important commodity and has high economic value. This study aims to determine the growth pattern of whitespotted guitarfish landed in the PPI Sungai Kakap. This research was conducted at the PPI Sungai Kakap, Sungai Kakap District, Kubu Raya Regency, West Kalimantan Province in July and August 2019. Data was collected by observation, surveys, and interviews. Data analysis of sex ratios, length, and weight was carried out on samples of whitespotted guitarfish. The results of the analysis of the sex ratio of male and female whitespotted guitarfish were 1.00:1.44, this shows that the number of male fish caught is relatively equal to the number of female fish caught. The results of the analysis of the length and weight relationship of whitespotted guitarfish, the a value is 20.643 and the b value is 0.6770. That value represents a negative allometric growth pattern for male and female fish. The negative allometrics explain that the length growth is faster than the weight growth. Generally, the increase of the length and weight is equal, but the whitespotted guitarfish has length growth faster than weight growth